Measuring Long-Run Exchange Rate Pass-Through - Olivier de Bandt; Anindya Banerjee; Tomasz Kozluk (Kiel Institute for the World Economy (IfW), 2007)
The paper discusses the issue of estimating short- and long-run exchange rate pass-through to import prices in euro area countries and reviews some problems with the measures recently proposed in the literature. Theoretical considerations suggest a long-run Engle and Granger cointegrating relationship (between import unit values, the exchange rate and foreign prices), which is typically ignored in existing empirical studies. We use time series and up-to-date panel data techniques to test for cointegration with the possibility of structural breaks and show how the long-run may be restored in the estimation. The main finding is that allowing for possible breaks around the formation of EMU and the appreciation of the euro starting in 2001 helps restore a long run cointegration relationship, where over the sample period the fixed component of the pass-through decreased while the variable component tended to increase.
Keywords: F42; F36; F31; F14; C23; 330; exchange rates; pass-through; import prices; panel cointegration; structural break